Self-Assessed Competence of Experienced Expatriate Nurses in a Rural and Remote Setting - Salah Aqtash; Walter Frederick Robb; Lyndal Heather Hunter; Majdi Almuhtasib; Abeer Hamad; Sharon Mary Brownie (SAGE Publishing, 2017)
We aimed to measure the self-assessed level of competence among nurses working in the public hospitals of Al-Gharbia Region, a remote rural region of United Arab Emirates, and to explore the factors associated with the nurses' self-perceived competency. The Nurse Competency Scale, which measures the self-assessed level of competency of nurses, has been validated in a variety of clinical settings, in facilities of various sizes, and in small and large cohorts. However, its application among an expatriate nursing workforce working in small hospitals and health facilities in remote and rural areas has not been examined. We used the Nurse Competency Scale to survey the nursing workforce in Al-Gharbia's public hospitals in United Arab Emirates. All 435 practicing registered nurses with more than 3 months clinical experience in the network were invited to participate. Data were collected electronically and analyzed by international collaborators. Statistical analysis included analysis of variance, Kruskal-Wallis, multiple linear regression, χ 2 test of independence, and Cronbach's α. Totally, 189 responses were analyzed (43.4% response rate). Overall self-assessed levels of competence were uniformly "very good" across all competence categories. The overall score (84.3) was higher than those found in most other studies. Frequency of use was the most outstanding variable influencing self-assessed competence. Total years of experience were the next significant variable. Some items of the scale were not yet applicable to activities in the region, particularly those relating to supervision of students. The high scores achieved by expatriate nurses in the small hospitals of Al-Gharbia reflect well on the rigor of the recruitment process, ongoing cross-training and functional competency assessment. Policies and practices aimed at recruiting experienced expatriate nurses and providing opportunities to use competencies continue to be critical in providing a quality nursing service in a rural and remote region.